Effect of Saccharomyces cerevisiae culture mitigates heat stress-related dame in dairy cows by multi-omics - Du, Dewei; Jiang, Wenbo; Feng, Lei; Zhang, Yu; Chen, Peng; Wang, Chengqiang; Hu, Zhiyong (Frontiers in Microbiology, 2022)
The effect of heat stress on ruminants is an important issue. In recent years, The growth of Chinese dairy industry has rapidly increased, generating RMB 468,738 million revenue in 2021. Decreased milk yield, which is the most recognized impact of heat stress on dairy cows and results in significant economic loss to dairy producers. Heat stress also lowers immunity and antioxidant capacity and changes the bacterial composition and metabolites of rumen. The purpose of this study is to investigate the effect of addition Saccharomyces cerevisiae culture on heat-stressed cows. The impact of S. cerevisiae culture on microbiota composition, functional profiles, and metabolomics was assessed in heat-stressed cows. Forty-five Holstein cows in mid-lactation were selected and randomly divided into three groups (15 cows per group). Groups D-C, D-A, D-B were fed the basal diet, the basal diet + first S. cerevisiae culture 100 g/d, the basal diet + second S. cerevisiae culture 30 g/d respectively. The trial lasted 60 days. There was an increased abundance of the Phylum firmicutes in the rumen of heat-stressed dairy cows fed with S. cerevisiae, of which four genera had significantly higher abundance, Ruminococcus_gauvreauii_group, Butyrivibrio_2, Moryella, and Ruminiclostridium_6. At the functional level, ten pathways differed significantly between the three groups (P<0.05), with an increase in fatty acid biosynthesis, fatty acid metabolism, PPAR signaling pathway, ferroptosis, and biotin metabolism in the treatment groups. More differential metabolites were found in the D-C and D-A groups than in the D-C and D-B groups. These results indicate that S. cerevisiae cultures can influence the health status of heat-stressed cows by modulating rumen microbial composition, function, and metabolites, thereby improving rumen cellulolytic capacity. This study can provide or offer suggestions or recommendations to the development and utilization of feed additives.